Pengaruh disiplin kerja karyawan, lingkungan kerja karyawan, dan kompensasi karyawan terhadap kepuasan kerja karyawan PT. Tradimun Mitra Sejahtera - Alvaritzi, Amirul Mukminin; Santoso, Bowo (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
Achieving organizational goals involves managing human resources (HR) by considering several important factors. Work discipline, work environment, employee protection and job satisfaction play a crucial role in this. This research is aimed at PT. Tradimun Mitra Sejahtera to analyze the effect of work discipline, work environment, and work pressure on employee job satisfaction. The research method used is saturated sampling method, in which secondary data and primary data are used. Primary data was obtained through a questionnaire filled out by 35 employees of PT. Tradimun Mitra Sejahtera. Partial Least Squares (PLS) analysis was used by researchers to analyze the data. The results of the study show that employee job satisfaction is positively and significantly influenced by work discipline and work pressure. However, it turns out that the work environment has a negative effect that is not significant on the job satisfaction of employees of PT. Tradimun Mitra Sejahtera.